Dicer is required for haploid male germ cell differentiation in mice. - Hanna M Korhonen; Oliver Meikar; Ram Prakash Yadav; Marilena D Papaioannou; Yannick Romero; Matteo Da Ros; Pedro L Herrera; Jorma Toppari; Serge Nef; Noora Kotaja (PLoS ONE, 2011)
BACKGROUND: The RNase III endonuclease Dicer is an important regulator of gene expression that processes microRNAs (miRNAs) and small interfering RNAs (siRNAs). The best-characterized function of miRNAs is gene repression at the post-transcriptional level through the pairing with mRNAs of protein-encoding genes. Small RNAs can also act at the transcriptional level by controlling the epigenetic status of chromatin. Dicer and other mediators of small RNA pathways are present in mouse male germ cells, and several miRNAs and endogenous siRNAs are expressed in the testis, suggesting that Dicer-dependent small RNAs are involved in the control of the precisely timed and highly organised process of spermatogenesis. PRINCIPAL FINDINGS: Being interested in the Dicer-mediated functions during spermatogenesis, we have analysed here a male germ cell-specific Dicer1 knockout mouse model, in which the deletion of Dicer1 takes place during early postnatal development in spermatogonia. We found that Dicer1 knockout testes were reduced in size and spermatogenesis within the seminiferous tubules was disrupted. Dicer1 knockout epididymides contained very low number of mature sperm with pronounced morphological abnormalities. Spermatogonial differentiation appeared unaffected. However, the number of haploid cells was decreased in knockout testes, and an increased number of apoptotic spermatocytes was observed. The most prominent defects were found during late haploid differentiation, and Dicer was demonstrated to be critical for the normal organization of chromatin and nuclear shaping of elongating spermatids. CONCLUSIONS/SIGNIFICANCE: We demonstrate that Dicer and Dicer-dependent small RNAs are imperative regulators of haploid spermatid differentiation and essential for male fertility.